Secrets of ancient cultures : - Braman, Arlette N. (John Wiley & Sons, Inc., 2004)
This book is filled with activities and projects that will show you how the ancient Inca people lived and played, as well as how they managed to create an empire that extended nearly 3,000 miles! You’ll learn about the bravery of Inca warriors as you construct a war shield. You’ll discover how the Inca created beautiful music with panpipes and dance bells–and you’ll make them yourself! You’ll get to prepare a tasty Inca dish called Andean stew. Plus, you’ll find lots of amazing Inca facts on topics ranging from history and religion to language, metalworking, and art. So get ready for lots of fun as you discover the ancient secrets of The Inca.